Identification and treatment of depressive disorders in older adults with cancer. Issue 5 (September 2019) - Saracino, Rebecca M.; Nelson, Christian J.
Abstract: The increasing number of older adults living with cancer will inevitably include vulnerable subgroups who experience a range of depressive symptoms throughout the care continuum. It is well established that depression can lead to decreased quality of life, poor treatment adherence, increased length of hospital stay and health service utilization, and in severe cases, suicide. Thus, clinicians working in oncology must be able to identify, conceptualize, and treat (or connect to services) the mental health concerns of their older patients. This brief review describes the unique etiologies, features, and treatments for depressive syndromes among older adults in the oncology setting, drawing on the literature and prevailing depression management guidelines from both psycho-oncology and geriatric depression research.